Changes in Pain Perception following Psychotherapy: The Mediating Role of Psychological Components - Susanna Zanini; Alessandra Voltolini; Gaia Gragnano; Emilia Fumagalli; Francesco Pagnini (Pain Research and Management)
Chronic pain is frequently associated with significant psychological issues, such as depression or anxiety. Psychological treatments, such as psychotherapy, can often alleviate both psychological and pain symptoms. However, there is limited research about the association between psychological symptoms and perceived pain in the context of psychotherapeutic interventions. We conducted a retrospective study that analyzed, in a hospital context, how changes in psychological functioning and well-being were associated with pain reduction. Thirty-seven records of patients with chronic pain attending psychotherapy in a public hospital were included. All patients were assessed before psychotherapy, as well as after 6 and 10 months, with self-reported questionnaires about pain, anxiety, depression, and psychological functioning. Results indicate that reductions in anxiety, depression, psychological problems, risk factors, and well-being are strongly related with a reduction in pain, further confirming the hypothesis that psychological morbidity is associated with pain severity.